2010
DOI: 10.1007/s11434-010-3095-6
|View full text |Cite
|
Sign up to set email alerts
|

U-Pb dating of detrital zircons from the Wudangshan Group in the South Qinling and its geological significance

Abstract: U-Pb dating was made by the LA-ICP-MS method for detrital zircons from the Wudangshan volcanic-sedimentary succession in the South Qinling. Samples comprise quartz sandstones of the Wudangshan Group collected from the base of the Yangping Formation and an upper layer of the Shuangtai Formation overlain its volcanic sequence, and two river-sand collections from the drainage systems cutting across the two formations, respectively. The results show that the Yangping detrital zircons are dominated by 830-780 Ma gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(43 citation statements)
references
References 40 publications
3
40
0
Order By: Relevance
“…Chen et al [20] recently identified emplacement ages of 2.7-2.6 Ga for A-type granites, which is similar to the age of 2693 ± 9 Ma obtained for the granite intrusion of the Yudongzi Group [21] and the protolith age of 2.75-2.70 Ga reported for the Huangluling granulite in the Dabie Mountain [22,23]. In fact, the age data of these three groups were also recorded in detrital zircons from metasedimentary rocks [5][6][7][8][9] and inherited zircons from igneous rocks [10][11][12][13][14] in different areas of the Yangtze craton, suggesting that the 3.3-3.2 Ga, 2.95-2.9 Ga and 2.7-2.6 Ga eras are important periods for the continental crustal growth in the Yangtze craton.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Chen et al [20] recently identified emplacement ages of 2.7-2.6 Ga for A-type granites, which is similar to the age of 2693 ± 9 Ma obtained for the granite intrusion of the Yudongzi Group [21] and the protolith age of 2.75-2.70 Ga reported for the Huangluling granulite in the Dabie Mountain [22,23]. In fact, the age data of these three groups were also recorded in detrital zircons from metasedimentary rocks [5][6][7][8][9] and inherited zircons from igneous rocks [10][11][12][13][14] in different areas of the Yangtze craton, suggesting that the 3.3-3.2 Ga, 2.95-2.9 Ga and 2.7-2.6 Ga eras are important periods for the continental crustal growth in the Yangtze craton.…”
Section: Discussionsupporting
confidence: 80%
“…The growing amount of isotopic age data from Archean to Paleoproterozic, particularly the recently published U-Pb zircon ages, has led many researchers to suggest that Archean crystalline basement is widespread beneath the Yangtze craton [4]. However, the supporting evidence mainly comes from U-Pb studies of detrital zircons in metasedimentary rocks [5][6][7][8][9] or inherited zircons in igneous rocks [10][11][12][13][14]. The Archean age information obtained for the exposed basement rock series are mostly from the Kongling high grade metamorphic terrane at the northern margin of the Yangtze craton [15][16][17][18][19][20], with sporadic reports from the granulites in the Yudongzi Group and the Dabie Mountains [21][22][23].…”
mentioning
confidence: 99%
“…The SCB position in Rodinia reconstruction has received much attention, whereas the Nd isotope stratigraphy of the Yangtze continental nucleus presented here provides an additional constraint on this issue. The results of the present study also indicate that the formation process of the SCB and its history involved in Rodinia breakup are likely more complicated than previously proposed, including the number of micro continents merged into the unified SCB and the extent of the primary SCB before the breakup [62].…”
Section: Discussionsupporting
confidence: 51%
“…The lower intercept age (ca. 800 Ma) may represent the time when the rock suffered a later thermal event, which also is consistent with the time of Neoproterozoic tectonothermal events in the Yangtze block, or even over the entire South China area [54][55][56][57][58][59][60][61][62][63].…”
Section: Zircon U-pb Age and Characteristics Of Rare Earth Element Comentioning
confidence: 79%